2007
DOI: 10.1161/circulationaha.106.674259
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification, Systematic Classification, and Anticipatory Management Strategies for Stent Fracture After Percutaneous Pulmonary Valve Implantation

Abstract: Background-We analyzed the incidence, risk factors and treatment options for stent fracture after percutaneous pulmonary valve (PPV) implantation (PPVI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
2
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(160 citation statements)
references
References 14 publications
3
153
2
2
Order By: Relevance
“…The Edwards valve has evolved over recent years, with an increased range of sizes including the 29-mm Sapien XT and, more recently, the Sapien S3 valve. Both valves are mounted on a balloon-expandable stent platform and require pre-stenting to create an optimal landing zone and reduce the chances of stent fracture or stenosis (for the Melody valve) of the framework after valve implantation [11][12][13]. For RVOT diameters >26-27 mm or patients with native RVOT post-transannular patch or very expansile RVOT, pre-stenting followed by implantation of these valves is very challenging.…”
Section: Limitation Of Currently Available Devicesmentioning
confidence: 99%
“…The Edwards valve has evolved over recent years, with an increased range of sizes including the 29-mm Sapien XT and, more recently, the Sapien S3 valve. Both valves are mounted on a balloon-expandable stent platform and require pre-stenting to create an optimal landing zone and reduce the chances of stent fracture or stenosis (for the Melody valve) of the framework after valve implantation [11][12][13]. For RVOT diameters >26-27 mm or patients with native RVOT post-transannular patch or very expansile RVOT, pre-stenting followed by implantation of these valves is very challenging.…”
Section: Limitation Of Currently Available Devicesmentioning
confidence: 99%
“…The most common complication has been stent fractures which occurred in 5% to 30% of cases. (14,15,19) Although the vast majority of stent fractures remain asymptomatic, it may lead to the development of outflow tract gradients. However, this can easily be treated with the implantation of another percutaneous valve.…”
Section: Coronary Compression Was Responsible For Virtually All Deathsmentioning
confidence: 99%
“…Another problem that can require reintervention is stent fracture, which has been reported to be as high as 43% without bare-metal stenting of the RVOT [31]. Nordmeyer et al [32] reported a 75% freedom from Melody stent fracture (MSF) at 2 years in the native RVOT. In the multicenter trial for Melody valve implantation [16], short and medium-term follow-up data demonstrated that the freedom from stent fracture was 83.7% ± 3.7% at 7.5 months and 77.8% ± 4.3% at 14 months.…”
Section: Potential Complicationsmentioning
confidence: 99%
“…The median follow up was 30 months. MSF was classified into three types according to Nordmeyer et al [32]: type 1, fracture of one or more strut without loss of stent integrity; type 2, fracture with loss of stent integrity; and type 3, fracture associated with separation of fragments or embolization. Thirtynine out of 150 patients were diagnosed with MSF; 33 patients were classified as type I.…”
Section: Potential Complicationsmentioning
confidence: 99%